Gamification for Student Achievement in Classroom: In Search of Requirement for Student Achievement Application - Rayinda Pramuditya Soesanto (International Journal of Innovation in Enterprise System, 2021)
There are numerous methods available in the education arena for increasing student participation in class. The experience that students have during class is critical not just for the students, but also for the instructor. Student achievement in the classroom can be increased to the point that the student enjoys performing class tasks. Problems arise when the students are burned out because they are exhausted by learning, especially online learning during the pandemic situation. It is necessary to develop an application that may be utilized as a tool to assist teachers and students in managing student achievement through the use of gamification. The objective of this study is to ascertain which requirements and functions should be incorporated into the design of the student achievement application. User centered requirement engineering approach is used in this research to elicit the requirement from the users. Lecturers and students were employed as respondents in this study to ascertain the development phase's priorities and essential functions. The application's functions and characteristics are separated into two broad categories: technical and usability / content. The Delphi technique is used to identify the function/characteristics. Further research could be conducted to develop systems / applications based on the functional requirements identified during the study in order to develop a student achievement application.